Model Asesmen Sumatif dengan Menggunakan Metode Library Research untuk Mata Pelajaran Pendidikan Agama Islam (PAI) pada Kurikulum Merdeka - Maisyaroh, Illusiyah; Abdullah, Muhammad; Hadi, Muhammad Nur (Asatiza: Jurnal Pendidikan, 2023)
The independent curriculum is still relatively new in the learning process, where many teachers are still not able to maximize the process of implementing the independent curriculum, especially in the realm of summative assessment for PAI subjects. The aim of this research is to find out what the summative assessment model for PAI subjects in the Merdeka curriculum is so that teachers can better understand the Merdeka curriculum. This research uses a qualitative approach with a library research method, where in the process of searching for data for this research, references will be used in literature studies. The results of this research are that the summative assessment model for PAI subjects in the independent curriculum has many steps and studies to be implemented. This research produced eight steps in summative assessment in the independent curriculum, namely (1) competency identification; (2) selection of assessment format; (3) assessment instrument specifications; (4) determining the assessment scale; (5) assessment scheduling; (6) the summative assessment is carried out according to schedule; (7) data processing and analysis; and (8) feedback and reporting.